Impact of Implementing the Lean Management on Internal Errors at an Outpatient Hospital Pharmacy in China - Lv L; Yao Y; Zhang M; Xin C (Patient Preference and Adherence)
Lisong Lv, Yi Yao, Mingwan Zhang, Chuanwei Xin Department of Pharmacy, Tongde Hospital of Zhejiang Province, Hangzhou, 310012, People’s Republic of ChinaCorrespondence: Chuanwei Xin, Department of Pharmacy, Tongde Hospital of Zhejiang Province, No. 234 Gucui Road, Xihu District, Hangzhou, 310012, People’s Republic of China, Tel +8657189972240, Fax +8657189972242, Email xcw373@163.comPurpose: The purpose of this study was to explore the lean management strategies used by an outpatient hospital pharmacy in China to reduce internal errors in prescription dispense and to describe their impact on patient satisfaction.Methods: The type and number of internal errors in prescription dispense from January 1, 2022, to December 31, 2022, were collected. The causes of these errors were analyzed based on a series of lean management concepts and methods, and Lean Management was implemented from January 1, 2023, to December 31, 2023, in this outpatient hospital pharmacy. The number of internal errors, the proportion of dispense errors and the change of patient satisfaction before and after Lean Management were compared.Results: Before the implementation of Lean Management, 2978 cases of internal errors were reported. It includes 1286cases (43.18%) of delivering wrong numbers, 612cases (20.55%) of medication in close proximity, 434cases (14.57%) of forget to dispense medication, 221cases (7.42%) of sound-alike medication, 203 cases (6.82%) of multiple sizes of a medication, 125 cases (4.20%) of look-alike medication, and 97 cases (3.26%) of others. The proportion of dispense errors was 3.46‰. After the implementation of Lean Management, the total number of internal errors in prescription dispense decreased to 219 cases, the proportion of internal errors in prescription dispense decreased to 0.27‰, which has a significant difference, and the satisfaction of patients increased from 52.94% to 72.97%.Conclusion: The implementation of Lean Management can be an efficient approach to reduce the internal errors in prescription dispense.Keywords: lean management, internal errors in prescription dispense, outpatient hospital pharmacy